Lessons from the Current Japanese Triple Helix Model - Hosono, Mitsuaki; Nakayama, Yasuo (School of Business and Management Institut Teknologi Bandung, 2012)
Since mid-1990s, the Japanese government has encouraged university-industry collaboration to foster innovations for economic growth. Learning from the American licensing model of technology transfer, Japanese Bay-Dole Act and TLO (Technology Licensing Organization) Act were enacted in late 1990s. In addition, the corporatization of Japanese National Universities (JNUs) in 2004 spurred their technology-transfer activities to obtain external funds. As a result, more than 50 TLOs has been established since FY1998, and also the number of patent application and licensed patents were increased at JUNs rapidly after FY2004. However, the licensing income has been stayed poor and some of TLOs were abolished. There are few evidences that the introduction of licensing model of technology transfer into Japan could contribute to innovation properly. Therefore, this study will try to clarify if licensing model of technology transfer work in Japan by analyzing the Japanese National University (JNU) patent. There are 20,485 applied patent, which invented by JNU’s researcher(s) from FY2004 to 2007. 38% of them were applied by solely by JNUs and 52% were by JNU and Private Firms etc. In the Japanese Patent Act, jointly applied patents are not licensed to the third party without the consent of co-applicant(s). Hence, more than half of the patent invented by JNU researchers is not basically used for patent licensing. Consequently, JNUs and TLOs face difficulties in patent licensing under the current Patent Act. Keywords: Technology Transfer, TLO, University Patent, Japan